The institutional determinants of CEO compensation: An international empirical evidence - Habib Jouber; Hamadi Fakhfakh (International Journal of Business Science & Applied Management (IJBSAM), 2011)
Corporate governance literature suggests that the relationship between CEO effort and outcomes such as firm performance is highly uncertain due to the influence of numerous organizational and environmental contingencies that are outside CEOs control. The major focus of this study is to determine whether institutional factors explain cross-sectional differences in CEO pay structure and sensitivity to performance and luck. Thus, we address three ultimate questions; Are CEOs rewarded for luck? Does institutional features matter for CEO pay for luck? How do systematic incentive effect is sensitive to lucks nature? Ordinary Least Squares (OLS) and Instrumental Variables (I.V.) estimations based on a sample of 300 publicly traded firms covering four countries from the Anglo-American and Euro-Continental corporate governance models between 2004 and 2008 show that the answers to the two first questions are a surrounding yes. Robustness check tests relying to the third question provide evidence that pay for luck is asymmetric. That is, executives are rewarded for good luck but they are safe of bad luck.
Keywords: 650; CEO compensation; performance; institutional factors; luck; corporate governance